Penerapan Kriptografi Keamanan Data Administrasi Kependudukan Desa Pagar Jati Menggunakan SHA-1 - Lisnayani Silalahi; Anita Sindar (Program Studi Teknik Informatika, Fakultas Teknik. Universitas Serambi Mekkah, 2020)
Data security and confidentiality is currently a very important issue and continues to grow. Several cases concerning data security are now a job that requires handling and security costs that are so large. To maintain the security and confidentiality of messages, data, or information so that no one can read or understand it, except for the rightful recipients, a data security system application with an encryption method using an algorithm is designed. The SHA-1 cryptographic hash function that takes input and produces a 160-bit hash value which is known as the message iteration is usually rendered as a 40-digit long hexadecimal number.